CHALLENGES OF ECONOMIC LAW IN THE GLOBAL AND DIGITAL ERA: ANALYSING REGULATION, DATA PROTECTION, AND CYBERSECURITY THROUGH A LITERATURE REVIEW - Loso Judijanto (CV. Adiba Aisha Amira, 2025)
The development of the digital economy in the era of globalisation has brought significant changes to the economic legal system, particularly in relation to regulation, data protection, and cybersecurity. This research aims to analyse the challenges of economic law in Indonesia in the face of digital transformation, with a focus on the effectiveness of regulations, implementation of personal data protection, and efforts to strengthen cybersecurity. The method used is a literature study with a juridical-normative approach, examining legislation, doctrine, and previous research results. The results of the study show that although Indonesia has a number of regulations such as the Personal Data Protection Law and regulations related to cybersecurity, their implementation still faces obstacles in the form of regulatory disharmony, weak law enforcement, and low digital literacy in society. In addition, the challenges of globalisation and rapid technological development require harmonisation of regulations across countries and increased capacity of human resources in the fields of law and technology. This research recommends strengthening the legal framework, increasing cross-sector collaboration, and public education to create a safe, fair and sustainable digital economy ecosystem.